Attrition of Hepatic Damage Inflicted by Angiotensin II with alpha-Tocopherol and beta-Carotene in Experimental Apolipoprotein E Knock-out Mice - Gopal, K.; Gowtham, M.; Sachin, S.; Ram, M.R.; Shankar, E.M.; Kamarul, Tunku (Nature Research, 2015)
Angiotensin II is one of the key regulatory peptides implicated in the pathogenesis of liver disease. The mechanisms underlying the salubrious role of alpha-tocopherol and beta-carotene on liver pathology have not been comprehensively assessed. Here, we investigated the mechanisms underlying the role of Angiotensin II on hepatic damage and if alpha-tocopherol and beta-carotene supplementation attenuates hepatic damage. Hepatic damage was induced in Apoe(-/-) mice by infusion of Angiotensin II followed by oral administration with alpha-tocopherol and beta-carotene-enriched diet for 60 days. Investigations showed fibrosis, kupffer cell hyperplasia, hepatocyte degeneration and hepatic cell apoptosis; sinusoidal dilatation along with haemorrhages; evidence of fluid accumulation; increased ROS level and increased AST and ALT activities. In addition, tPA and uPA were down-regulated due to 42-fold up-regulation of PAI-1. MMP-2, MMP-9, MMP-12, and M-CSF were down-regulated in Angiotensin II-treated animals. Notably, alpha-tocopherol and beta-carotene treatment controlled ROS, fibrosis, hepatocyte degeneration, kupffer cell hyperplasia, hepatocyte apoptosis, sinusoidal dilatation and fluid accumulation in the liver sinusoids, and liver enzyme levels. In addition, PAI-1, tPA and uPA expressions were markedly controlled by beta-carotene treatment. Thus, Angiotensin II markedly influenced hepatic damage possibly by restraining fibrinolytic system. We concluded that alpha-tocopherol and beta-carotene treatment has salubrious role in repairing hepatic pathology.